E-CIGARETTES A BENEFIT OR BARRIER TO SUCCESSFUL CESSATION FOR OLDER SMOKERS? - Cataldo, J (Innov Aging, 2018)
In the U.S., there has been great progress in the reduction of adult smoking prevalence however, in the last decade, the smallest reduction has occurred among older adults (>45 yo), and there has been no change for those >65 yo. Between 2000 and 2015, past-year cigarette smoking quit attempts increased for younger adult smokers (< 45 yo). However, there was a decrease in both past-year quit attempts and successes for older smokers; these rates are likely due to older smoker’s: overestimation of smoking’s benefits, underestimation of their ability to quit smoking, lack of awareness of cessation’s full benefits at any age; and more recently, the increasing prevalence of e-cigarette use among older current and former cigarette smokers. This paper explores associations between older smokers’ attitudes and beliefs about e-cigarettes and tobacco use behavior by conducting a secondary analysis on data from a 2014 cross-sectional survey of a random national sample of 498 current smokers (>45 years). The 108 current e-cigarette users believed e-cigarettes help people quit cigarettes (p < .001); are safer than cigarettes (p = .002); and are acceptable to friends (p = .010) and family (p = .007). Important findings: 1) most older smokers wanted to quit cigarettes; 2) among e-cigarette users, most believed e-cigarettes are healthier than cigarettes and are effective for cessation, and 3) the perception of social acceptability modified tobacco use behavior by influencing initiation and maintenance of both conventional cigarette and e-cigarette use.